Effect of Contact Lens Wear on Cornea - Ammer, Rabia (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine contact lens induced corneal changes among contact lens users. Study Design: Cross-sectional study. Place and Duration of Study: This study recruited the sample from Madinah Teaching Hospital Faisalabad, E Plomer Optics and Punjab Optics Lahore. The study was conducted in 4 months from 05 April to 5 August 2016. Materials and Methods: Data of 100 contact lens users was collected. Corneal changes were observed by using slit lamp and fluorescein strips. SPSS version 23 was used for data analysis. Descriptive and inferential statistics were reported for variables. Results: 58 (58%) of contact lens users had corneal changes. Significant association of corneal changes were found with years of contact lens use (X2 = 31.636; p = .000) and minus power of contact lens (X2 =14.325; p = .000). No significant association (p > 0.05) of corneal changes were found with type of contact lens, daily wearing time of contact lenses and plus power of contact lenses. Neovascularization was found in 38% of contact lens users followed by corneal staining in 33%, corneal infiltrates in 17% and corneal abrasions in 12%. Conclusions: It was concluded that long term use of contact lenses induced many corneal changes among contact lens users. Key Words: contact lens, corneal changes, neovascularization, infiltrates, staining, abrasion.